JUDICIAL REASONING IN THE USE OF ON-SITE INSPECTION (DESCENTE) TO DETERMINE CHILD CUSTODY - Laily, Affi Nurul; Hartono, Bambang (Universitas Nusa Cendana, 2026)
This study examines the use of local inspection (descente) by judges in child custody disputes at the Religious Court, particularly in Decision Number 677/Pdt.G/2024/PA.Tgm. The research focuses on the legal reasoning behind conducting a direct inspection of a child’s living environment and how the results contribute to judicial evidence in ensuring the best interests of the child. Normatively, the authority of the Religious Court in custody cases is regulated under Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law, as well as Law Number 7 of 1989 concerning Religious Courts and its amendments. Local inspection (descente) itself is governed by procedural rules such as Article 180 RBg/153 HIR and Supreme Court Circular (SEMA) No. 7 of 2001, primarily aimed at uncovering material truth. Using an empirical legal method with a qualitative approach, data were collected through document analysis and in-depth interviews with judges and related parties. The findings reveal that although descente is traditionally applied to physical objects, its extension to observing a child’s condition and environment is a progressive judicial practice. Through this process, judges are able to obtain objective and direct insights into the child’s living situation—information that cannot be fully captured through documents or witness testimony alone. From a legal standpoint, the results of the local inspection hold free evidentiary value (vrij bewijskracht), which may develop into judicial presumption and strengthen the judge’s conviction in making decisions. In conclusion, local inspection (descente) plays a vital role in safeguarding children’s rights by ensuring decisions are based on comprehensive and factual considerations. However, more specific technical regulations are needed to standardize its implementation and enhance legal certainty in future custody cases. Keywords: Child Custody; Local Inspection (Descente); Best Interest of the Child